2013
DOI: 10.1007/s10151-013-1068-x
|View full text |Cite
|
Sign up to set email alerts
|

Defecatory disorders in anorexia nervosa: a clinical study

Abstract: Defecatory disorders are associated with anorexia nervosa and increased with the duration and severity of the illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 17 publications
4
25
0
Order By: Relevance
“…The frequency of 27.6% for constipation in patients with AN is in accordance with findings by Boyd, Abraham, and Kellow (2005) (24%) and more than twice as high as in the general population (12%) (Mugie et al, 2011), but lower than reported by Sileri et al (2014) The association between constipation and AN is in line with other findings regarding constipation, weight, BMI, and eating problems. A nationwide Swedish twin study revealed a large association between restrictive eating habits and gastrointestinal disorders (Täljemark, Råstam, Lichtenstein, Anckarsäter, & Kerekes, 2017).…”
Section: Frequency Of Constipationsupporting
confidence: 89%
“…The frequency of 27.6% for constipation in patients with AN is in accordance with findings by Boyd, Abraham, and Kellow (2005) (24%) and more than twice as high as in the general population (12%) (Mugie et al, 2011), but lower than reported by Sileri et al (2014) The association between constipation and AN is in line with other findings regarding constipation, weight, BMI, and eating problems. A nationwide Swedish twin study revealed a large association between restrictive eating habits and gastrointestinal disorders (Täljemark, Råstam, Lichtenstein, Anckarsäter, & Kerekes, 2017).…”
Section: Frequency Of Constipationsupporting
confidence: 89%
“…In a study of 85 individuals suffering from AN, 93% were diagnosed with defecatory disorders; noteworthy, the percentage of defecatory disorders rose to 75% when the illness lasted ≥5 years and even to 100% when body mass index (BMI) was <18 kg/m 2 (Sileri et al, 2014). Furthermore, 83% suffered from constipation, 84% from obstructed defecation syndrome, 64% from a combination of constipation and fecal incontinence, and 9% from fecal incontinence alone (Sileri et al, 2014).…”
Section: Gi Complaints In Anmentioning
confidence: 99%
“…In a study of 85 individuals suffering from AN, 93% were diagnosed with defecatory disorders; noteworthy, the percentage of defecatory disorders rose to 75% when the illness lasted ≥5 years and even to 100% when body mass index (BMI) was <18 kg/m 2 (Sileri et al, 2014). Furthermore, 83% suffered from constipation, 84% from obstructed defecation syndrome, 64% from a combination of constipation and fecal incontinence, and 9% from fecal incontinence alone (Sileri et al, 2014). On average, the subjects with AN reached a score of 10 ± 5 in the Wexner constipation score (cut-off: <5), 12 ± 4 in the Altomare's obstructed defecation score (cut-off: <10), and 12 ± 9 in the fecal incontinence severity index (cut-off: <10; Sileri et al, 2014).…”
Section: Gi Complaints In Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Constipation is nearly universal in AN, arising from the same calorie‐conservation strategy that causes gastroparesis: the body does not spend limited calories on nonessential functions. Slowed GI transit time allows more water absorption from the colon, worsening constipation, while pelvic floor dysfunction contributes to difficulties with defecation .…”
Section: Casesmentioning
confidence: 99%